CULTIVATING CHARACTER EDUCATION FOR PROSPECTIVE ELEMENTARY SCHOOL TEACHERS THROUGH ELEMENTARY SOCIAL STUDIES COURSES - Rosyida, Desy Anindia; Saputri, Zuana Della (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
The role of elementary school teachers is not only to transfer knowledge, but also to contribute to the formation of students' character. One of the pillars of the success of character education is the realization of ideal elementary school teacher candidates. The cultivation of character education can be done in various ways, one of which is through the learning of elementary social studies courses. So it is hoped that the learning from the elementary social studies course will help students in shaping the character that prospective elementary school teachers must have. This research uses descriptive qualitative research. Qualitative descriptive research is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior from data sources. This research was conducted at the Balitar Islamic University campus for PGSD students. The research stages include: observation, interviews, documentation. The current condition of the Indonesian nation and state encourages the government to prioritize character education in national development to realize the vision of national development, which is to create a society with noble character, morality, ethics, culture, and civility based on the Pancasila philosophy. Character values ​​must be instilled by elementary school teachers since they follow the education of prospective elementary school teachers so that they can transmit these values ​​to their students in the future. Character education for prospective elementary school teachers is carried out using an integrated approach in all subjects.